Persecutory delusions: developing the understanding of belief maintenance and emotional distress. - Freeman, D; Garety, P; Kuipers, E (2001)
BACKGROUND: The objective of the study was to develop the cognitive understanding of persecutory delusions. It was hypothesized that safety behaviours contribute to the persistence of persecutory delusions by preventing disconfirmation. It was further hypothesized that emotional distress is associated with aspects of the content of delusions. An investigation was designed to establish whether individuals with persecutory delusions use safety behaviours, and to test predicted associations between delusion content and emotional distress. METHOD: A cross-sectional investigation was conducted on 25 individuals with persecutory delusions. A detailed assessment was made of the presence of safety behaviours, the content of delusions and emotional distress. RESULTS: All participants had used at least one safety behaviour in the last month, most typically avoidance. Higher levels of anxiety were associated with greater use of safety behaviours. New data were obtained on the content of persecutory delusions. Aspects of the content of the delusions were associated with levels of depression, self-esteem, anxiety and delusional distress. CONCLUSIONS: Individuals with persecutory delusions use safety behaviours. The findings may develop the understanding of delusion persistence, acting upon delusions and the negative symptoms of schizophrenia. There are implications for cognitive interventions for psychosis. Support was also found for the hypothesis that emotional distress is linked to the content of delusional beliefs; it is speculated that prior emotional distress influences the content of delusions, and that delusion content in turn influences levels of emotional distress.